Masalah Etika Dan Hukum Kesehatan Pada Layanan Kesehatan Publik Atau Rumah Sakit “Aborsi” - Putri Widya Herman; Annisa Wahyuni (AKADEMI PEREKAM DAN INFORMASI KESEHATAN (APIKES) IRIS PADANG, 2023)
Abortion is a sensitive issue that involves law, ethics, and human life. This research investigates the legal framework governing abortion, including changes in the 2023 Health Law that updated previous provisions. Abortion is a medical procedure often used to terminate unwanted pregnancies, but it is also considered a hazardous medical practice for pregnant women. The study also reveals that in Indonesia, maternal deaths are primarily caused by hemorrhage, hypertension during pregnancy, and infections in pregnant women, with abortion being one of the major contributors to maternal hemorrhage. Amid controversies surrounding abortion, several illegal clinics have been uncovered, performing thousands of unauthorized abortions in recent years. In terms of law, the research discusses relevant regulations in the Indonesian Penal Code (KUHP) and the Health Law. Legal matters in Indonesia are marked by debates and contradictions in perceptions and understandings of existing laws, leading to underground abortion practices carried out by both formal and informal healthcare providers, whether compliant with medical standards or not. Method: This research employs a systematic review method, utilizing data sources obtained from the internet, including research journals, academic papers, and news articles focused on the ethics and legal aspects of healthcare in the context of abortion. Results: The findings of this research indicate that abortion significantly impacts women's health, with unsafe illegal abortion practices posing life-threatening risks. Additionally, legal interpretations of abortion, particularly in cases involving rape victims, vary. Conclusion: This research underscores the need for clear and harmonious abortion-related policies in Indonesia, as well as a strong understanding of ethics and morals among medical professionals. Consequently, efforts to implement more comprehensive and supportive legislative changes must persist to effectively address the ethical and legal issues surrounding abortion.